Seasonal trends in underwater ambient noise near St. Lawrence Island and the Bering Strait. (August 2020) - Southall, Brandon L.; Southall, Hugh; Antunes, Ricardo; Nichols, Ross; Rouse, Andrew; Stafford, Kathleen M.; Robards, Martin; Rosenbaum, Howard C.
Abstract: We measured spatial and temporal patterns of ambient noise in dynamic, relatively pristine Arctic marine habitats and evaluate the contributions of environmental and human noise sources. Long-term acoustic recorders were deployed around St. Lawrence Island and the Bering Strait region within key feeding and migratory corridors for protected species that are inherently important to Native Alaskan cultures. Over 3000 h of data from 14 recorders at nine sites were obtained from October 2014 to June 2017. Spatial and temporal ambient noise patterns were quantified with percentile statistics in 1/3rd-octave bands (0.02–8 kHz). Ice presence strongly influenced ambient noise by influencing the physical environment and presence of marine mammals. High variability in noise was observed within and between sites, largely as a function of ice presence and associated factors. Acute contributions of biological and anthropogenic sources to local ambient noise are compared to monthly averages, demonstrating how they influence Arctic soundscapes. Highlights: High variability in ambient noise was observed within and between sites. Seasonal variability in ambient noise as well as site-specific differences were evident. Ice presence strongly influenced ambient noise by influencing the physical environment and biological presence. Acute biological and human sounds relative to typical ambient noise demonstrate influences on Arctic soundscapes.